Pengaruh Non Performing Loan (NPL) dan Capital Adequacy Ratio (CAR) terhadap Profitabilitas (Studi Kasus pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2010-2013) - Putrianingsih, Dwi Indah; Yulianto, Arief (Management Analysis Journal, 2016)
The purpose of this study was to know the influence level of Non Performing Loan (NPL) and Capital Adequacy Ratio (CAR) towards the profitability (ROA) in banking companies listed in BEI. The population in this research is the entire banking company registered in BEI in 2010-2013. Research of sampling is performed using the method of purposive sampling. Analysis technique used are multi liniear regression of ordinary least square and hypotheses test used is t-statistic. Based on the results of the survey, encountered that Non Performing Loan (NPL) influenced negative toward profitability. Capital Adequacy Ratio (CAR) influential effect negatively to profitability. Suggestions from this study is banking in Indonesia should maintain the continued level of capital has improved even more capital because it can increase the profit of capital adequacy that is ROA. And then minimize bad debts or reduce the value of pon performing loan, because with the declining value of non performing loan will increase the profits obtained by the ROA.